Analisis Pengelolaan Keuangan Usaha Mikro Kecil dan Menengah Berdasarkan SAK EMKM di Toko Nabila Desa Sitail Kecamatan Jatinegara Kabupaten Tegal - Fauziah Fauziah; Suryanto Sosrowidigdo (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
MSMEs are productive businesses that stand alone, which are carried out by individuals who meet the criteria for MSMEs as stipulated in Law Number 20 Article 1 of 2008. Nabila shop sells daily necessities. To run the business, financial management must be done well, and the purpose of this study is to find out the financial management practices of Nabila shop. Qualitative descriptive methodology was used in this study. Three data collection methods were used: documents, interviews, and observations. This research found that Nabila shop has an automated accounting system that only tracks sales transactions. It does not have a liability account on the balance sheet and income statement, and does not provide notes to the financial statements. the researcher recommends that using the accounting application that is already available in the store properly and correctly, doing complete recording and bookkeeping and having detailed and accurate financial reports. And the owner and staff Nabila shop should attend training on the application of SAK EMKM as a whole at the Tegal Regional Cooperative, MSME and Industry Office so that they can fully implement the three components of SAK EMKM and can also explore learning information on the internet. .